Comparison of Northern Bobwhite Chick Fecal and Crop Analyses - Kristen Utz; John P. Carroll; Steven J. Moreby (National Quail Symposium Proceedings, 2017)
Impacts of modem agriculture on gamebird brood ecology have been studied in a number of species. One common factor cited has been the decline in available invertebrate food available to foraging chicks. In the United Kingdom, assessment of chick diet has been accomplished mainly through fecal analysis of wild chicks, whereas in North America crop analysis of human-imprinted chicks has become a commonly applied technique. We compared results of both techniques on groups of human-imprinted northern bobwhite (Colinus virginianus) chicks to determine if these different techniques provide similar results. Chicks were allowed to forage in groups of 6-8 in cotton fields with various cover crops. We euthanized half the chicks for crop analysis and isolated the other half of the chicks for 12 hours to collect feces. We found a positive relationship between total number of invertebrates/chick in crops and feces (P = 0.01, R2 = 0.51). However, among important chick-food Orders the relationship varied greatly: Coleoptera (P = 0.10, R2 = 0.34), Homoptera (P < 0.001, R2 = 0.41), and Hymenoptera (P = 0.81, R2 = 0.05). Our results suggest that there is a positive relationship between the 2 techniques, but that composition of the diet relative to what foods might be available in a particular site could be biased. We suggest more detailed research on technique development and standardization of techniques for assessing this important component of bobwhite life history.
Keywords: brood habitat; chicks; Colinus virginianus; fecal analysis; Georgia; insects; northern bobwhite